LEGAL POLICY OPTIMIZING PREMARITAL GUIDANCE AS AN EFFORT TO REDUCE DIVORCE RATES - Husein, Saddam; Yumarni, Ani; Ma’arif, Rizal Syamsul; Qolyubi, Asep Thobibuddin; Syabanti, Siti; Khairiyyah, Fitriani Hasna (Fakultas Hukum Universitas Djuanda, 2024)
The high divorce rate in Indonesia, especially in the Bogor Regency area, indicates that there is still a need for special attention from the Ministry of Religion to reduce the divorce rate. There were recorded 6,261 divorce cases throughout 2023 which occurred in the Bogor Regency Religious Court area. Efforts and strategies to reduce the divorce rate have been Many things are done, one of which is by holding pre-marital guidance for prospective brides and grooms who are about to get married. The aim of this research is to provide recommendations regarding the optimization of pre-marital coaching to create an eternal household. This research uses qualitative methods with stages of reviewing laws, observation, interviews, questionnaires, analysis and conclusions. The results of research on pre-marital guidance must first become a necessity and obligation and provide strict sanctions to prospective brides and grooms who do not follow pre-marital guidance. Second, pre-marital coaching for all candidates is attempted to be carried out for 16 hours of study in order to achieve the ideal target of coaching. Third, guarantee the availability of pre-marital guidance books and provide and require prospective couples to read them to completion before the marriage contract takes place.